Business Spirits: Religion and Business as Co-constitutive Phenomena - Gaitanidis, Ioannis (Implicit religion, 2022)
What are the co-making processes that blur the boundaries between religion and economy? How can we move past misleading metaphors and analogies that reify the false distinction between sacred and secular or that frame religion as pure essences corrupted by financialization? Inspired by McLaughlin et al.'s (2020) call for increased attention to the "corporate form of religion," we outline how common social structural and aspirational elements undergird shared processes of both religion-making and corporation-making. Drawing on ethnographic and historical data from contributing authors to this Special Issue, we hypothesize that the reification of religion and business is context dependent, benefits regimes of power, and is open to contestation; and that some intentional communities, purposeful or not, have from their inception been understood as neither religious nor corporate. We marshal global data from diverse case studies to explore the modes of relatedness between religions and corporations, on the one hand, and the context-specific boundary-making practices that reify a false binary, on the other.